2022
DOI: 10.1101/2022.08.18.504477
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution of giant pandoravirus from small icosahedral viruses revealed by CRISPR/Cas9

Abstract: Giant viruses (GVs) are a hotspot of unresolved controversies since their discovery, including the definition of Virus and the existence of a fourth domain of life1-3. While increasing knowledge of genome diversity has accumulated4, functional genomics was largely neglected. Here, we describe an experimental framework to genetically modify nuclear GVs and its host Acanthamoeba castellanii using CRISPR/Cas9, allowing us to uncover the evolution from small icosahedral viruses to amphora-shaped GVs. Ablation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…It has been proposed that this accessory partition is a hotspot of frequent gene loss and gain through HGTs (Senkevich et al 2021), but the few HGT identified in Pithoviridae does not support this model. In Pandoraviridae, core and essential genes, and those whose proteins are identified in the viral particle, are mostly localized in the left part of the genome, while accessory genes are located on the right part (Legendre et al 2018;Bisio et al 2022). This likely reflects ongoing genome increase involving de novo gene creation (Legendre et al 2018) and accelerated gene duplications (Bisio et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that this accessory partition is a hotspot of frequent gene loss and gain through HGTs (Senkevich et al 2021), but the few HGT identified in Pithoviridae does not support this model. In Pandoraviridae, core and essential genes, and those whose proteins are identified in the viral particle, are mostly localized in the left part of the genome, while accessory genes are located on the right part (Legendre et al 2018;Bisio et al 2022). This likely reflects ongoing genome increase involving de novo gene creation (Legendre et al 2018) and accelerated gene duplications (Bisio et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In Pandoraviridae, core and essential genes, and those whose proteins are identified in the viral particle, are mostly localized in the left part of the genome, while accessory genes are located on the right part (Legendre et al 2018;Bisio et al 2022). This likely reflects ongoing genome increase involving de novo gene creation (Legendre et al 2018) and accelerated gene duplications (Bisio et al 2022). In all cases, the dichotomous genome partitioning might also be linked to the epigenetic transcriptional regulation of core genes, through a peculiar 3D structure of this genomic region.…”
Section: Discussionmentioning
confidence: 99%